2008
DOI: 10.1080/13674670801978634
|View full text |Cite
|
Sign up to set email alerts
|

Representation of mental illness in Christian self-help bestsellers

Abstract: The present study examined messages about mental illness in 14 contemporary Christian self-help bestsellers. Content analysis revealed that most texts focused upon depression. Categories of textual units included Underlying Assumptions Regarding Depression, Representations of Depression, Roots/Causes/Reasons for Depression, and Christian Responses to Depression. Demonic influence was the most frequently cited reason for depression. Other reasons included negative cognitions, failure as a Christian, and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 60 publications
2
16
1
Order By: Relevance
“…This differs greatly from previous research in which the majority of participants reported that they attend services weekly (Caplan et al, 2013;Dunn & O'Brien, 2009). While it is possible to suggest that demographic factors, such as greater acculturation or lack of an ethnic enclave, could explain this absence of religious participation, another possibility consistent with the literature (Copel, 2008;Webb, Stetz & Hedden, 2008;Webb & Whitmer, 2001) is that some religious teachings served to invalidate their lived experiences which these women felt were at the root of their depression. Some participants believed that religious leaders would not understand their experiences and would attribute their depression to causes that these women did not endorse.…”
Section: Discussioncontrasting
confidence: 65%
“…This differs greatly from previous research in which the majority of participants reported that they attend services weekly (Caplan et al, 2013;Dunn & O'Brien, 2009). While it is possible to suggest that demographic factors, such as greater acculturation or lack of an ethnic enclave, could explain this absence of religious participation, another possibility consistent with the literature (Copel, 2008;Webb, Stetz & Hedden, 2008;Webb & Whitmer, 2001) is that some religious teachings served to invalidate their lived experiences which these women felt were at the root of their depression. Some participants believed that religious leaders would not understand their experiences and would attribute their depression to causes that these women did not endorse.…”
Section: Discussioncontrasting
confidence: 65%
“…that You will keep and protect them from the evil one" (Meyer, 2006(Meyer, , p. 1720 In raising the spectre of the supernatural as a means to self-actualisation and wellbeing, our findings concur in part with and develop Webb, Stetz & Hedden's (2008) content analysis of Christian self-help bestsellers, which showed that Biblical teaching frequently refers directly and indirectly to what can be considered 'psychological disorders' (Webb, 2017) -specifically mood disorders: anxiety, depression, post-traumatic disorders, bi-polar. Indeed, Meyer frequently using the word 'epidemic' to refer the prevalence to these disorders across the population.…”
Section: Mental Healthsupporting
confidence: 63%
“…One study examined books by Joel Osteen, Joyce Meyer, Nancy Leigh DeMoss, Beth Moore and others (Webb, Stetz, & Hedden, 2008). Content analysis demonstrated that demonic forces were Downloaded by [] at 10:13 16 May 2015 cited more often than any other potential source of depression.…”
Section: Working Lay Theologies Of Mental Illnessmentioning
confidence: 97%